Desarrollo de un sistema de Internet de las Cosas Industrial para el monitoreo de temperatura de un pasteurizador de leche (2023)
This document describes the design and implementation of an Internet of Industrial Things system for temperature monitoring in a milk pasteurization plant. For this, the recognition of the characteristics of the ideal temperature variables for the elaboration of the coastal serum, a general study of the architectures of monitoring systems will be carried out. Its adjustment and final tests to determine its real applicability. The development of this project allowed real-time monitoring of the variables of the cloud storage system, which allowed access to the diagnosis of the temperature of the pasteurization process by the end user.